The effect of using varied methods in the islamic religious education for the happy feelings of Madrasah Ibtidaiyah teacher (Study at KKM-MI Pandeglang-Banten Regency) - Eneng Humaeroh (Institute of Computer Science (IOCS), 2023)
This study aims to find out how the teachers of Madrasah Ibtidaiyah who use varied methods in learning Islamic Religious Education Subjects find that their students experience increased learning activities and involvement in the classroom. The use of varied methods also has an impact on increasing the acquisition of student learning scores. The teachers said they felt happy because their students experienced a significant increase in learning. This research was conducted in ten Madrasah Working Groups (KKM) Madrasah Ibtidaiyah (MI) in Pandeglang Regency, Banten Province, with research respondents of teachers of Islamic Religious Education subject clusters randomly selected. The method used in this study is a field survey method using observation instruments, interviews, and documentation. The results of this study showed that almost all respondents expressed feelings of happiness and felt new challenges in teaching. The use of varied methods can liven up the classroom, foster an atmosphere of curiosity, and realize a child-centered learning system (Student Center Learning). The use of varied methods is a learning model that has novelty value and is expected to produce other learning models.